PENGEMBANGAN MEDIA BIMBINGAN BERBASIS WEBSITE UNTUK MENINGKATKAN KESEHATAN MENTAL PADA MAHASISWA PROGRAM STUDI PASTORAL KONSELING IAKN TORAJA - Fernita Sari Gala; Abdullah Sinring; Muhammad Anas (Institut Agama Kristen Negeri Toraja, 2023)
This study aims to develop a website-based advice medium prototype to educate students, particularly those enrolled in the Pastoral Counseling Study Program at IAKN Toraja, on mental health. To address the research objectives, the researchers employed the Research and Development methodology outlined by Borg and Gall, adapted to suit the specific requirements of the product under development. Researchers initiated the study by commencing a requirement assessment, followed by executing data collecting, formulating an initial product design, validating the design through expert testing, revising the plan based on feedback, running a limited trial, and then revising the product. The website bestieku.org was developed and evaluated by professionals in the field. The assessments received from these experts varied. Specifically, BK experts provided highly positive evaluations, with a percentage of 91.07%. Reviews from media and education experts were generally positive, with a rate of 75%. In the interim, the practical examination administered to counseling practitioners yielded a commendable qualification, attaining a percentage of 79.16%. Based on a small-scale exam conducted on a cohort of 20 students, a notable level of proficiency was achieved, as evidenced by an 85% success rate. Based on the findings, implementing a website-based guidance media prototype holds significant potential in enhancing the mental well-being of students. Tujuan penelitian ini ialah menghasilkan prototipe media bimbingan berbasis website untuk mengedukasi mahasiswa tentang kesehatan mental, khususnya pada mahasiswa Program Studi Pastoral Konseling IAKN Toraja. Untuk menjawab tujuan penelitian, maka peneliti menggunakan metode Research and Development (R & D) dari Borg dan Gall yang telah dimodifikasi sesuai dengan produk yang sedang dikembangkan. Peneliti memulai penelitian dengan melaksanakan need assessment (analisis kebutuhan), selanjutnya melaksanakan pengumpulan data, rancangan produk awal, validasi desain (uji ahli), revisi desain, uji coba terbatas dan revisi produk. Produk yang dihasilkan ialah website bestieku.org dan dari validasi para ahli diperoleh penilaian yang cukup beragam yakni ahli BK memberi kualifikasi sangat baik dengan persentase 91,07%, ahli media dan pendidikan memberi penilaian baik dengan persentase 75%. Sedangkan pada uji praktisan dari praktisi BK diperoleh kualifikasi praktis dengan persentase 79,16%, sedangkan dari 20 orang mahasiswa yang diuji pada kelompok kecil, diperoleh kualifikasi sangat baik dengan persentase 85 %. Jadi dapat disimpulkan prototipe yang dikembangkan berupa media bimbingan berbasis website untuk meningkatkan kesehatan mental pada mahasiswa sangat praktis dan sangat layak untuk digunakan.